Switzerland : Financial Sector Assessment Program; Factual Update; Insurance Sector Market and Regulatory Developments. (IMF Staff Country Reports; Country Report, 2007)
This paper presents a factual update of the Insurance Core Principles including insurance sector market and regulatory developments for Switzerland. Regulatory reforms since 2003 have updated Switzerland's regulatory and supervisory regime for the insurance industry to bring it in line with international best practices. The Insurance Supervision Law (ISL) has reoriented the regulatory focus and expanded the regulatory scope to include group/conglomerate supervision, corporate governance, risk management, and market conduct of insurance intermediaries. The ISL also provides for a range of corrective and preventive regulatory measures.